Movement Control of Three Omni-Wheels Robot using Pole Placement State Feedback and PID Control - Swadexi Istiqphara; Ulya Darajat, Anisa; Fahmizal; Ferdous, Mohammad Farhan (Peneliti Teknologi Teknik Indonesia, 2023)
Omni wheels robot have high efficiency in robot movement, but also have its own challenges in controlling this robot, especially robots with three omni wheels (3WD). This paper proposes a robot control system using the pole placement state feedback method to control the inner loop which controls the body reference speed, and PID method is used to control the outer loop which controls the robot's position in world coordinates. The results obtained using computer simulations show that the proposed method is able to control the robot's position in world coordinates even though there is an overshoot of 5- 10% on X and yaw axis, however the Y axis performance is overshoot more than 100% because of coupled effect thats still cannot be eliminated.